Neurological complications of left atrial myxoma: a case report on stroke with left atrial myxoma and postoperative brain metastasis and cerebral aneurysm - Ai, Xudong; Shao, Qingqing; Tian, Xueyan; Zhou, Yicheng; Zhou, Tiantian (Frontiers in Neuroimaging, 2024)
Atrial myxoma is a rare benign tumor that can cause a variety of complications, including cerebral infarction. We present a case of a 52-year-old female patient who developed cerebral infarction caused by an atrial myxoma. The patient underwent successful surgical resection of the tumor, and the infarction was managed accordingly. However, 15-months post-surgery, the patient developed new neurological symptoms. Imaging studies revealed multiple cerebral metastases, consistent with the possibility of seeding of tumor cells. This rare complication emphasizes the importance of long-term monitoring after the resection of atrial myxomas. The occurrence of metastasis in the brain, though rare, should be considered in follow-up care, particularly in patients who have had embolic events related to atrial myxomas. Our case highlights the potential for cerebral myxoma metastasis even after initial successful surgical intervention, underscoring the need for comprehensive follow-up and vigilant monitoring of such patients.